PLACING ANTIMICROBIAL RESISTANCE IN THE CONTEXT OF COMPETING PUBLIC HEALTH PRIORITIES IN SUB-SAHARAN AFRICA, A PERSPECTIVE FROM MALAWI - Nicholas Feasey (International Journal of Infectious Diseases, 2023)
Antimicrobial resistance is a major threat to human health that is predicted to impact most heavily on sub-Saharan Africa, however there is a lack of clinical outcome data from drug-resistant infections in this setting. There are reasons to expect the COVID-19 pandemic to have both positive and negative impacts on AMR in Africa. We have recruited a series of prospective longitudinal cohorts from Queen Elizabeth Central Hospital (QECH), Blantyre, Malawi and the surrounding communities in the Southern Region of Malawi. The data from these cohorts has been used to describe the aetiology of febrile illness, the burden of antimicrobial resistance in this setting and the distribution of extended spectrum beta-lactamase producing bacteria in humans, animals and the environment. Amongst a cohort of patients presenting to QECH unwell with febrile illness, 67% were living with human immunodeficiency virus (HIV). We identified a diagnosis in 145 of 225 (64%) participants, most commonly tuberculosis (TB; 34%) followed by invasive bacterial infections (17%), arboviral infections (13%), and malaria (9%). In a second cohort with drug resistant infection, resistance to third-generation cephalosporins was associated with an increased probability of in-hospital mortality (hazard ratio [HR] 1·44, 95% CI 1·02–2·04), longer hospital stays (1·5 days, 1·0–2·0) and decreased probability of discharge alive (HR 0·31, 0·22–0·45). In the community cohorts, a paucity of environmental health infrastructure and materials for safe sanitation was identified across all sites and ESBL-Enterobacterales were isolated from 41.8% of human stool, 29.8% of animal stool and 66.2% of river water samples and was associated with the wet season, living in urban areas, advanced age and in household-animal interactions. Life threatening febrile illness is common in Blantyre however, diagnostics are few, however the COVID-19 pandemic has led to rapid expansion of diagnostic capacity. We are, however frequently treating the wrong bugs with ceftriaxone, further there was significant expansion of azithromycin demand and usage during the pandemic. Current management of sepsis has not been optimised and ceftriaxone use is promoting carriage of ESBL bacteria out of the hospital and ESBL E. coli and K. pneumoniae are ubiquitous in the community, where environmental hygiene infrastructure and community antimicrobial stewardship are critically lacking.